2021
DOI: 10.3389/fpubh.2020.633340
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Community Social Determinants of Health Associated With Diabetes Management in a Mexican American Population

Abstract: Background: Diabetes is a major health burden in Mexican American populations, especially among those in the Lower Rio Grande Valley (LRGV) in the border region of Texas. Understanding the roles that social determinants of health (SDOH) play in diabetes management programs, both at the individual and community level, may inform future intervention strategies.Methods: This study performed a secondary data analysis on 1,568 individuals who participated in Salud y Vida (SyV), a local diabetes and chronic disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This study observed that, at a marginally significant level ( p < 0.1), older adults exhibited better glycemic control, potentially due to a lower degree of insulin resistance and higher participation/engagement in programs [ 2 ]. Furthermore, being female showed a marginal association with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study observed that, at a marginally significant level ( p < 0.1), older adults exhibited better glycemic control, potentially due to a lower degree of insulin resistance and higher participation/engagement in programs [ 2 ]. Furthermore, being female showed a marginal association with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, being female showed a marginal association with diabetes. However, previous research among Mexican-origin individuals residing in the US–Mexico border has not provided conclusive evidence regarding the relationship between sex and diabetes [ 2 , 4 , 25 , 26 , 29 ]. Notably, one study found that females had higher levels of physical activity, while males were more likely to adhere to a daily healthy eating plan; both physical activity and a daily healthful eating plan are strongly related to diabetes prevention and management [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LEA rates in the United States, for example, have dropped significantly among the elderly, with only minor decreases among the young and middle-aged. The number of LEAs continues to be higher among non-Whites and male residents in the United States, with significant geographic differences [ 43 ].…”
Section: Reviewmentioning
confidence: 99%